2016
DOI: 10.1371/journal.pone.0161950
|View full text |Cite
|
Sign up to set email alerts
|

β2-Glycoprotein I Inhibits Vascular Endothelial Growth Factor-Induced Angiogenesis by Suppressing the Phosphorylation of Extracellular Signal-Regulated Kinase 1/2, Akt, and Endothelial Nitric Oxide Synthase

Abstract: Angiogenesis is the process of new blood vessel formation, and it plays a key role in various physiological and pathological conditions. The β2-glycoprotein I (β2-GPI) is a plasma glycoprotein with multiple biological functions, some of which remain to be elucidated. This study aimed to identify the contribution of 2-GPI on the angiogenesis induced by vascular endothelial growth factor (VEGF), a pro-angiogenic factor that may regulate endothelial remodeling, and its underlying mechanism. Our results revealed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 62 publications
0
11
0
1
Order By: Relevance
“…Growth factors such as VEGF bind to its receptors VEGFR1 and VEGFR2 and activate downstream signaling pathways of oxidative stress mediated various kinases such as p38MAPK, AKT, and JNK, which are important regulators of endothelial cell activation [ 56 , 57 ]. Chiu et al have shown that β 2-glycoprotein-I prevents VEGF-induced HAEC growth as well as migration by regulating the activation of ERK1/2 and AKT [ 58 ]. Further, Shu et al have shown that vasostatin prevents endothelial cell growth by activation of caspase-3 and downregulation of eNOS in HUVEC cells [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Growth factors such as VEGF bind to its receptors VEGFR1 and VEGFR2 and activate downstream signaling pathways of oxidative stress mediated various kinases such as p38MAPK, AKT, and JNK, which are important regulators of endothelial cell activation [ 56 , 57 ]. Chiu et al have shown that β 2-glycoprotein-I prevents VEGF-induced HAEC growth as well as migration by regulating the activation of ERK1/2 and AKT [ 58 ]. Further, Shu et al have shown that vasostatin prevents endothelial cell growth by activation of caspase-3 and downregulation of eNOS in HUVEC cells [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15] We showed previously that purified β 2 -GPI inhibits cell migration, proliferation, and angiogenesis in human aortic endothelial cells. [9][10][11] However, the role of natural β 2 -GPI in tumor development remains unknown. The present study showed that β 2 -GPI is a negative regulator of cell migration, proliferation, and invasion in melanoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Western blot analysis was carried out as previously described. 11 In brief, cells were lysed in RIPA buffer and cell extracts were separated by centrifugation at 12 000 g for 20 minutes at 4°C. Nuclear extracts were prepared for analysis of nuclear p50 and p65 levels.…”
Section: Western Blot Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…A ação sobre a angiogênese é apenas uma parte das funções fisiológicas descritas para a β 2 GPI e a multiplicidade de seus efeitos reitera as vias de sinalização intracelular como prováveis alvos bioquímicos para sua função. Diversos autores relataram o efeito da proteína sobre a angiogênese, tanto in vitro quanto in vivo (Rakic et al, 2003;Beecken et al, 2006;Sakai et al, 2007;Nakagawa et al, 2009;Passam et al, 2010b;Machado et al, 2013;Chiu et al, 2016). A abordagem utilizada neste trabalho não permitiu atribuir uma via alvo específico para os efeitos anti-angiogênicos da proteína.…”
Section: Discussionunclassified